Financial Management Literacy for Students of Economic Education FKIP UKSW - Jean Belynda Lalihatu; Dwi Iga Luhsasi; Carolina Lita Permatasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Financial literacy is an important part of the realization of student management in relation to improving financial literacy so that it creates knowledge and behavior in financial management that has been carried out so far. Students need to realize financial management by increasing financial literacy which is what they learn during lectures. Therefore, students are able to carry out financial management with the existence of financial literacy. This research was conducted at the SWCU FKIP Economic Education using a qualitative method with a snowball sampling technique and with data collection techniques, namely primary data, interviews and documentation, which aims to determine student literacy towards financial management of SWCU FKIP economic education students. The results of this study indicate that students already understand the basics of finance but there are several things that must be underlined in financial literacy, namely knowledge of investment and insurance which is still low as well as sources of financial literacy that only rely on lecture material even though there are still many media that can be accessed to add student financial literacy such as books, social media and websites. The results of students who are still low on understanding financial literacy make their financial management ineffective. On the other hand, students who have an understanding of financial literacy become more effective in financial management, it can be concluded that the importance of financial literacy itself for students.